2008
DOI: 10.1016/j.ijpara.2007.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Gender-enriched transcription of activation associated secreted proteins in Ostertagia ostertagi

Abstract: Activation associated secreted proteins (ASP) are members of a nematode-specific protein family belonging to the SCP/Tpx-1/Ag5/ PR-1/Sc7 family. Three different types of molecules have been identified in this family: two-domain ASPs and single-domain ASPs showing homology to either the C-terminal or N-terminal domain of the two-domain ASP. The function of these proteins is still unclear, but a role in transition to parasitism and a role as allergen are often suggested. Here we report that the abomasal cattle p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Adult ES proteins in O. ostertagi identified a homologue of an ASP and a vitellogenin [92], which were not identified in T. circumcincta ES proteins [101]. However, we have successfully identified a globin-like protein and Na-ASP-2 - a PR-1 protein from Necator americanus ) [102] and ASP-3 from O. ostertagi [103]. ASPs are the members of a group of nematode-specific molecules [5].…”
Section: Discussionmentioning
confidence: 99%
“…Adult ES proteins in O. ostertagi identified a homologue of an ASP and a vitellogenin [92], which were not identified in T. circumcincta ES proteins [101]. However, we have successfully identified a globin-like protein and Na-ASP-2 - a PR-1 protein from Necator americanus ) [102] and ASP-3 from O. ostertagi [103]. ASPs are the members of a group of nematode-specific molecules [5].…”
Section: Discussionmentioning
confidence: 99%
“…VAL-1 also has significant sequence homology with venom allergens from vespid wasps (Ag5) and fire ants (Ag3). 30 A study by Visser et al 32 showed that VAL-1 and its homolog may have a role in the reproductive development of the male Ostertagia worms. Thus the VAL-1 homolog appears to be important for the establishment and survival of the parasite in the host 20 and may have a possible role in immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…SCP/TAPS belong to a large group of proteins that include the Ancylostoma -secreted proteins (ASPs; Cantacessi et al, 2009b). In parasitic nematodes, ASPs were first characterized for hookworms (Hawdon et al, 1996, 1999) and subsequently from related strongylid nematodes (Visser et al, 2008). As ASPs are abundant in the excretory/secretory (ES) products of the infective L3, they are thought to play an important role in the transition from the free-living to the parasitic stage of a nematode during its invasion of the host (Hawdon et al, 1996, 1999; Moser et al, 2005; Datu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%